2009
DOI: 10.1136/oem.2008.043281
|View full text |Cite
|
Sign up to set email alerts
|

Roles of age, length of service and job in work-related injury: a prospective study of 446 120 person-years in railway workers

Abstract: Objectives Because work-related injuries are common and yet the mechanisms through which various types of injuries relate to age, length of service and job remain unknown, this study assessed the role of age, length of service and job in work-related injury. Methods Prospective study of all 164 814 permanently employed male workers at the French national railway company during 1998e2000, based on the company's injury database: 446 120 person-years, 15 195 injuries with working days lost, coded using the compan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 34 publications
1
25
1
2
Order By: Relevance
“…In addition, future studies including factors outside of work will be important. The higher risk of work-related injuries in younger workers has been reported in Western countries 1,17,26,40,41) . Some previous studies on workers in some industries reported that age was a risk factor for LBP 8,33,42,43) , while other studies reported no association between age and LBP 8,39) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, future studies including factors outside of work will be important. The higher risk of work-related injuries in younger workers has been reported in Western countries 1,17,26,40,41) . Some previous studies on workers in some industries reported that age was a risk factor for LBP 8,33,42,43) , while other studies reported no association between age and LBP 8,39) .…”
Section: Discussionmentioning
confidence: 99%
“…As for personal factors, female gender 13,14) and younger age (<25 yr 15,16) , <30 yr [17][18][19] ) or older age (≥40 17) ) have been reported as risk factors. Health-related risk factors such as obesity 20) , sleep disorders 18,21,22) and smoking habit 8,18,21) are also indicated.…”
Section: Introductionmentioning
confidence: 99%
“…Østerlund et al factors sensitive to age are thus important and should be interpreted carefully, especially for worker-related factors (46).…”
Section: Work-practice-related Factorsmentioning
confidence: 99%
“…Ressalta-se que tal associação foi significativa mesmo controlando o efeito do tempo de serviço, enfraquecendo, portanto, a hipótese relacionado ao efeito do trabalhador sadio. As características dos trabalhadores relacionadas à geração talvez tenham influenciado tal resultado (Chau et al, 2010).…”
Section: Eventos Extralaboraisadversos E Casos Prováveis De Tept Em Bunclassified